2018
DOI: 10.1111/iwj.12931
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the skin blotting method when used on the elderly

Abstract: The aim of this study was to compare protein secretion on intact skin of extremities and verify the relationship between the marker proteins on abdominal skin and systemic factors using skin blotting. A cross-sectional study was conducted among elderly patients aged 65 years and older (N = 73) at a long-term medical facility in Japan. Skin blotting was performed on the right and left forearms, right and left lower legs, and abdomen. Pearson's correlations and Bland-Altman plots were utilised for comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Koyano et al verified no difference in the bilateral protein secretion on the intact skin of extremities for type IV collagen (COL-4), matrix metalloproteinase-2 (MMP-2), and tumour necrosis factor-alpha (TNF-α). 28 The paper demonstrated that systemic (e.g., age) and local factors (e.g. environmental exposures) influenced the intensity levels of COL4 and MMP-2 on the extremities while systemic factors influenced abdominal COL4 and MMP-2 (but not TNFα).…”
Section: Significance and Variationsmentioning
confidence: 94%
See 4 more Smart Citations
“…Koyano et al verified no difference in the bilateral protein secretion on the intact skin of extremities for type IV collagen (COL-4), matrix metalloproteinase-2 (MMP-2), and tumour necrosis factor-alpha (TNF-α). 28 The paper demonstrated that systemic (e.g., age) and local factors (e.g. environmental exposures) influenced the intensity levels of COL4 and MMP-2 on the extremities while systemic factors influenced abdominal COL4 and MMP-2 (but not TNFα).…”
Section: Significance and Variationsmentioning
confidence: 94%
“…Koyano et al disallowed ointments or bathing the day before sampling to avoid disturbing protein balance. 28 Higuchi et al allowed daily bathing but did not permit moisturisers. 29 Sari et al reported blotting at least 30 min after ablutions or 1 h after bathing, and participants were asked to avoid skincare product applications.…”
Section: Significance and Variationsmentioning
confidence: 99%
See 3 more Smart Citations